Internatos, casas, escolas, seminários, universidades: - Oliveira, Marina Rodrigues de (2023)
The time period between the decades of 1870 and 1890 corresponds, simultaneously, to a gradual legal arrangement of the education in Brazil, as well as to the inception of connoisseurs of the national literature. In light of this, the present work aims to verify the relevance to the narrative, including the pertinent pedagogic transformation of a total of 25 novels published in the aforementioned period, that depicts the school or equivalente environments, as well as the actors involved and matters arriving from the Applied didactics. In furtherance of this interest, the chosen literary works were read and analyzed, based on the Literary Criticism and History of Education literature studies, and it was found that, in addition to bringing, to the literary field, the most germane issues to the topic addressed, the narratives also contribute to strong critics extended to the country ́s social organization.